2019
DOI: 10.1142/s1088424619500925
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical properties of porphyrinic covalent cages endowed with different flexible linkers

Abstract: In-depth photophysical studies of four flexible covalent cages bearing either two free-base porphyrins or one free-base porphyrin and one Zn(II) porphyrin, connected by linkers of different lengths, are reported. In the case of the cages with two free-base porphyrins, exciton coupling between the porphyrins is evidenced by large and split Soret bands in the absorption spectra, but the different length of the linkers has only a slight effect on their emission properties. Strong electronic interactions between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(30 citation statements)
references
References 43 publications
3
27
0
Order By: Relevance
“…The emission titration, performed upon excitation at the isosbestic point, shows a progressive decrease of the fluorescence of the cage ( Figure 3 b), supporting the formation of metalated porphyrins, which are known to be weakly emissive with respect to their free-base counterparts. 42 The luminescence lifetime at the end of the first step of titration was found to be 8.4 ns, which is thus only slightly decreased with respect to the value of 9.0 ns measured for the original cage 29 and attributable to the residual fluorescence of the nonmetalated cages, likely interacting with silver(I) in their lateral groups.…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…The emission titration, performed upon excitation at the isosbestic point, shows a progressive decrease of the fluorescence of the cage ( Figure 3 b), supporting the formation of metalated porphyrins, which are known to be weakly emissive with respect to their free-base counterparts. 42 The luminescence lifetime at the end of the first step of titration was found to be 8.4 ns, which is thus only slightly decreased with respect to the value of 9.0 ns measured for the original cage 29 and attributable to the residual fluorescence of the nonmetalated cages, likely interacting with silver(I) in their lateral groups.…”
Section: Resultsmentioning
confidence: 72%
“…We previously showed that the emission properties of the free-base component in Zn-S-2H are strongly affected by the presence of the closely spaced Zn-porphyrin counterpart, with the result of an almost halved quantum yield and a reduced lifetime (6.7 vs 8.5) with respect to the model monomer and cage 2H-S-2H , attributed to a change in the molecular symmetry or to an increased intersystem crossing rate induced by the close proximity of the Zn center. 29 The recovery of the free-base emission intensity observed upon the addition of Ag(I) testifies the separation of the two units, following the complexation of the Ag(I) ions with the lateral triazole groups ( Figure 6 ). Indeed, the lifetime of the free-base emission measured at 720 nm for the complex was found to be 7.9 ns, which is closer to the value of 8.5 ns for the free-base porphyrin unaffected by the Zn counterpart.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Different hexacoordinated Co(III)Cl porphyrins with pyridine and epoxide as axial ligands can be involved in this reaction [18f,22b,27] and the distance between the two metal centres can be adjusted due to the flexible linkers. [19,28] For the epoxide ring-opening step, a cooperative action of the two catalytic sites in which one axial chloride ligand promotes intramolecular ring opening of the epoxide bound to the other Co(III) site could account for the increased catalytic activity. [29] Noteworthy, whereas Co(III) porphyrins are not able to catalyse this reaction in absence of a co-catalyst, a yield of 13 % was obtained with the cage.…”
Section: Catalytic Activity Of (Cocl) 2 -1 In the Synthesis Of Cyclicmentioning
confidence: 99%